Implementation of Bai 'Bitsaman Ajil Financing Sanctions in Baitul Maal Wat Tamwil (BMT) Pahlawan Tulungagung to Delay in Installment Payments - Fathur Rohman Albanjari; Rokhmat Subagiyo (The Pontianak State Institute of Islamic Studies, 2022)
This research aims to know applying sanctions and penalty on financing ba’i bitsaman ajil at the BMT Pahlawan Tulungagung for the delay in payment of the installments. The author's methods of research conducted in this study using a qualitative approach. As for the type of research is descriptive, meaning that the data collected is in the form of words, images, and not the numbers. The results showed that the application of fines in BMT Pahlawan Tulungagung is in compliance with the Shariah Board Fatwa of the national assemblies of scholars of Indonesia No. 17/DSN-MUI/IX/2000. In its application of fines charged to borrowers who can afford but procrastinate the payout as well as clients who do not have good faith to settle the payment.